What drives corporate water disclosure? The role of board composition in Brazil and India - Alan Bandeira Pinheiro; Nágela Bianca Do Prado; Gustavo Hermínio Salati Marcondes de Moraes (Sustainable Environment)
We aimed to examine the effect of board composition on corporate water performance. Our study was exploratory and had a quantitative approach, which used secondary data from the Refinitiv Eikon database. 668 Brazilian and Indian publicly traded companies were analysed from 2016 to 2020. While the dependent variable was corporate water performance, the independent variables selected were board size, board gender, board independence, and corporate social responsibility committee. Results presented empirical evidence that board size, board independence, and the presence of a CSR committee positively affect water performance in the basic materials, energy, industrial, and utilities sectors. We also demonstrated, by a moderating effect, that companies disclose water more entirely in less corrupt countries, as lower corruption levels intensify the positive effect of board independence on water disclosure. Public and regulatory authorities should hold a positive attitude toward companies that report on water information, give them more attention and support, and stimulate companies to disclose more in their environmental reports. Furthermore, the research develops a water performance index that is less susceptible to greenwashing, and the study combines a symmetric method (panel data regression) and an asymmetric approach (fuzzy set qualitative comparative analysis) techniques.